The tuberization signal StSP6A represses flower bud development in potato - Plantenga, Faline D M (Journal of experimental botany, 2019)
Potato (Solanum tuberosum L.) can reproduce sexually through flowering and asexually through tuberization. While tuberization has been thoroughly studied, little research has been done on potato flowering. Flower bud development in the strictly short-day tuberizing S. tuberosum group Andigena is impaired under short-day conditions. This impaired development may indicate that tuberization negatively influences flowering. Here, we determine how tuberization affects flower bud development. To find out whether the absence of tubers improves flowering, we prevented tuberization by: (i) grafting potato scions onto wild potato rootstocks, which were unable to form tubers; (ii) removing stolons, the underground structures on which tubers form; and (iii) using plants that were silenced in the tuberization signal StSP6A. Additionally, transgenic plants with increased StSP6A expression were used to determine if flower bud development was impaired. The absence of a tuber sink alone did not accelerate flower bud development, nor did it allow more plants to reach anthesis (open flowering stage) or have more open flowers. Interestingly, reducing StSP6A expression improved flower bud development, and increasing expression impaired it. Our results show that flower bud development in potato is repressed by the tuberization signal StSP6A, and not by competition with the underground tuber sink